2017
DOI: 10.1038/s41598-017-00314-5
|View full text |Cite
|
Sign up to set email alerts
|

Formyl peptide receptors promotes neural differentiation in mouse neural stem cells by ROS generation and regulation of PI3K-AKT signaling

Abstract: This study aimed to determine whether formyl peptide receptors (FPRs) regulated the differentiation of neural stem cells (NSCs). FPRs promote the migration of NSCs both in vitro and in vivo. However, the role of FPRs during differentiation of NSCs is unknown. Analysis by Western blot showed significantly increased expression of FPR1 and FPR2 during differentiation of NSCs. The activation of FPRs promotes NSCs to differentiate into neurons with more primary neurites and branch points and longer neurites per cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 73 publications
5
38
0
Order By: Relevance
“…Thus the reductions in total axonal and dendritic length are directly due to the effects of inhibiting FPR2 signalling when exposed to WRW4 or PBP10. Results are consistent with recent studies which show that FPR2 is expressed in hippocampal neural stem cells, and promotes differentiation into neurons with more and longer primary neurites per cell [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 93%
“…Thus the reductions in total axonal and dendritic length are directly due to the effects of inhibiting FPR2 signalling when exposed to WRW4 or PBP10. Results are consistent with recent studies which show that FPR2 is expressed in hippocampal neural stem cells, and promotes differentiation into neurons with more and longer primary neurites per cell [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 93%
“…This observation extends previous findings on the increased levels of glial ALX/FPR2 in the injured brain of Alzheimer's disease patients [28], where it seems that this glial receptor is involved in amyloid-β internalization [29]. Furthermore, in the study of Wang and colleagues, the presence of ALX/FPR2 was also observed in pyramidal neurons in different regions of the hippocampus, with a particular role in promoting migration and differentiation of neural stem cells in both rats and mice [30,31]. Our lack of detection of this receptor on axotomized neuronal cells and on microglia suggests that the heterogeneity in the pathophysiology, the type of neuronal population affected, and the species considered may account for the observed differences.…”
Section: Discussionsupporting
confidence: 88%
“…The RvD1 effects are likely mediated via the ALX/FPR2 receptor, expressed in both glial cells and neurons. This receptor's expression is heterogeneous and varies according to cell type, brain area and even the pathologic state of the brain tissue 26,49,72,73 , suggesting that both neurons and microglia could mediate the protective effects of RvD1 either directly or indirectly via release of soluble factors. Our previous finding of a RvD1mediated mechanism for halting neuroinflammation via activation of ALX/FPR2 receptor-regulated miRNAs 49 suggests that this circuit might also be involved in Syn rats.…”
Section: Discussionmentioning
confidence: 99%